Mining of seed coat cracking related genetic loci and genes in diverse soybean (Glycine max) populations. (25th January 2023) - Chu, Jiahao; Huang, Meihong; Zhang, Hua; Shao, Zhenqi; Sun, Yaqian; Rong, Shaoda; Li, Wenlong; Li, Xihuan; Zhang, Caiying
Abstract: Seed coat cracking (SCC) is a major factor that affects seed appearance quality, pathogen infection, humility absorption and seed storage in soybean. In view of this, a recombinant inbred line (RIL) population and a natural population were genotyped by SoySNP6K and were evaluated for type‐I SCC percentage. Eight QTLs were identified on six chromosomes with phenotypic variation explanations ranging from 3.46% to 34.71% in RIL population. Twenty‐three SNPs associated with cracking percentage were identified on eight chromosomes in natural population. More importantly, the association SNP ss715593768 in natural population was the left marker of qSCC‐C2‐1 in RIL population, which were detected across all of the environments and BLUP values. Two genes, Glyma.06G197300 and Glyma.06G202100, were proposed in this QTL region. These two genes showed differential expressions at seed developmental stages between RIL parents in the seed transcriptome sequencing and quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) analysis, and also showed differential expressions between two germplasms with different cracking percentage in natural population. Thus, the results provide novel insight into the genetic basis and molecular improvement of SCC in soybean.